Constructing an Index of Difficulty for Air Traffic Control Using Proximity Parameters. (2015) - Nagaoka, Sakae; Brown, Mark
Abstract: In this paper, we propose an approach to constructing an index of air traffic control difficulty based on exponential functions of proximity parameters of aircraft pairs, i.e. the time to closest point of approach and miss distance. The index is given by single value between 0 and 1 in order to simplify its presentation, such as in a heat map. The approach deals with the mapping of aircraft trajectory information onto proximity parameters and the derivation of the real-valued index in [0, 1]. The approach consists of the following steps: 1) Formulation of the concept of a difficulty index calculated from the trajectories of a pair of aircraft at a given time; 2) Determination of an objective function which evaluates the projected difficulty; and 3) Derivation of the difficulty index as a function of the trajectory information and model parameters. This paper briefly describes the method of mapping and some results from numerical calculation examples using the proposed method.